2023
DOI: 10.1080/22221751.2023.2195020
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine suppresses intestinal SARS-CoV-2 infection via a BNIP3-dependent autophagy blockade

Abstract: SARS-CoV-2, the causative virus of COVID-19, continues to threaten global public health. COVID-19 is a multi-organ disease, causing not only respiratory distress, but also extrapulmonary manifestations, including gastrointestinal symptoms with SARS-CoV-2 RNA shedding in stool long after respiratory clearance. Despite global vaccination and existing antiviral treatments, variants of concern are still emerging and circulating. Of note, new Omicron BA.5 sublineages both increasingly evade neutralizing antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Previous reports in human cell lines have demonstrated that LC3+ vesicles can be trafficked for secretion ( 46 , 69 ). In line with these reports, using the standardized autophagy reporter human cell line ( 26 , 50 , 70 ), we observed that fluorescently-labeled intracellular LC3+ vesicles can be released extracellularly ( Supplementary Figure 4 ). Markedly, subsequent immunophenotypical characterization of secreted vesicles by human DCs demonstrated that an average of 26% of the total population of CD9/CD81/CD63+ DC-derived EVs co-expressed the autophagy-associated LC3 marker ( Figures 7C, D ).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Previous reports in human cell lines have demonstrated that LC3+ vesicles can be trafficked for secretion ( 46 , 69 ). In line with these reports, using the standardized autophagy reporter human cell line ( 26 , 50 , 70 ), we observed that fluorescently-labeled intracellular LC3+ vesicles can be released extracellularly ( Supplementary Figure 4 ). Markedly, subsequent immunophenotypical characterization of secreted vesicles by human DCs demonstrated that an average of 26% of the total population of CD9/CD81/CD63+ DC-derived EVs co-expressed the autophagy-associated LC3 marker ( Figures 7C, D ).…”
Section: Resultssupporting
confidence: 85%
“…Human DCs are one of the first immune cells to encounter DENV upon a mosquito bite, and due to their migratory capacity and instruction of T cell responses they have been implicated in the facilitation of DENV systemic infection and dengue associated inflammation ( 11 14 ). We and others have shown that autophagosomes and autophagy pathways play key defensive or pro-viral roles during viral replication depending on the virus in question ( 26 , 38 , 41 , 46 , 50 ), however the role of autophagy pathways during DENV replication in primary human DCs remains unexplored. First, we confirmed that primary human DCs were infected with DENV-2/16681, as indicated by the presence of the early viral non-structural protein NS3 ( Figures 1A, B ) and viral dsRNA ( Figure 1C ), the latter of which forms as an intermediate during replication of the +ssRNA viral genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that SARS-CoV-2 exploits host autophagy machinery for intestinal dissemination[ 23 , 24 ]. Furthermore, Cloherty et al [ 25 ] proofed that Berbamine, a selection of autophagy-blocking drugs, can suppress intestinal SARS-CoV-2 infection as well as prevent SARS-CoV-2-mediated disruption of the intestinal barrier via an autophagy-mediated BNIP3 mechanism. However, not all viruses have evolved such an escape mechanism.…”
Section: Autophagy and Gi Physical Barrier Functionmentioning
confidence: 99%